Risk factors for the occurrence and persistence of coronary aneurysms in Kawasaki disease - Soo-kyeong Jeon (Korean Journal of Pediatrics, 2019)
Purpose Prognostic factors of coronary aneurysms in Kawasaki disease have been investigated in many studies. The aim of this study was to identify risk factors associated with early and late coronary artery outcomes in treated patients with Kawasaki disease. Methods A total of 392 patients diagnosed with Kawasaki disease from January 2012 to December 2015 in Pusan National University Children’s Hospital were retrospectively selected as subjects of the present study to determine risk factors for coronary aneurysms and persistence of coronary aneurysms after a 1-year follow-up. Results Coronary aneurysms were detected in 30 of 392 patients within 1 month after the occurrence of Kawasaki disease. Coronary aneurysms persisted in 5 of 30 patients after a 1-year follow-up. A long duration of fever (adjusted odds ratio [OR], 1.47; 95% confidence interval [CI], 1.06–2.02; P=0.018) and high platelet count (adjusted OR, 1.00; 95% CI, 1.00–1.01; P=0.009) were found to be independent factors to predict the development of coronary aneurysms in the early phase. Initial coronary severity (adjusted OR, 46.0; 95% CI, 2.01–1047.80; P=0.016) and a high white blood cell count (adjusted OR, 1.17; 95% CI, 1.01–1.36; P=0.028) were found to be significant factors for the persistence of late coronary aneurysms in univariate analysis. However, no significant factors were found in multivariate analysis. Conclusion These data are from early and late follow-up of coronary aneurysms in our unit. Further studies are needed to determine the mechanisms involved in the disappearance of coronary aneurysms and related factors.